POLA-POLA ZONAL SITUS-SITUS ARKEOLOGI - Ph. Subroto (Berkala Arkeologi, 1995)
The term Zonal patterns used in this paper refers to the notion of patterns shown by the distribution of sites from a spatial aspect. In this sense, the term zonal patterns is also used in the same sense as the term spatial patterns. By distribution, site locations in space show certain patterns, which are assumed to be related to a subsistence strategy. This means that the choice of the location of a site is related to efforts to minimize the use of energy and time in exploiting and distributing sources of subsistence. Because these sites represent human activities, the location where they exist can provide an overview of the natural environment and its technology. In some cases, the location of sites also reflects site types.